ASESMEN PERKEMBANGAN BAHASA ANAK USIA DINI DI TK PERTIWI DUWET - Zahrah Aulia (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Abstract. ASESMENT OF EARLY CHILDHOOD LANGUANGE DEVELOPMENT IN PERTIWI TK. Developmental assessment is the process of systematically collecting data/information on aspects of a child's development of a competency, based on evidence, allegedly influencing academic achievement. While development is the process of development in children, the direction of progress is well regulated within humans, then the children themselves are 4-5 years old. Where children still have exploration in child development, assessments carried out in early childhood aim to detect children's development from an early age, so that parents and teachers can easily provide the right stimulus and intervention for children. In this case the assessment is needed as a way of seeing the implementation of the development of mindsets, this study aims to explain the concepts and principles of assessment at the PAUD level. This research is a type of research that goes directly to Pertiwi Duwet Kindergarten. Meanwhile there are also 4 (four) assessment instruments or techniques at the PAUD level as the main part of the assessment concept, namely: anecdotal notes, work checklists, and photo series. Assessment of students at the PAUD level can be done in various ways, not arbitrarily. certain mastery.Keywords: Asesment, Development, Early ChildhoodAbstrak. ASESMEN PERKEMBANGAN BAHASA ANAK USIA DINIDI TK PERTIWI DUWET. Asesmen perkembangan adalah proses pengumpulan data/informasi secara sistematis terhadap aspek – aspek perkembangan anak terhadap suatu kompetensi, berdasarkan bukti – bukti, diduga berpengaruh terhadap prestasi akademik. Sedangkan perkembangan adalah proses perkembangan pada anak, arah kemajuan nya yang diatur dengan baik di dalam diri manusia, lalu anak sendiri yang memiliki usia 4 – 5 tahun. Dimana anak masih mempunyai explorisasi dalam perkembangan anak, Asesmen yang dilakukan pada anak usia dini bertujuan untuk mendeteksi perkembangan anak sejak dini, sehingga orang tua dan guru dengan mudah memberikan stimulus dan intevensi yang tepat pada anak. Dalam hal ini esesmen diperlukan sebagai cara dalam melihat implementasi perkembangan pola pikir, penelitian ini bertujuan untuk menjelaskan konsep dan prinsip asesmen pada jenjang PAUD, Penelitian ini merupakan jenis penelitianterjun langsung ke TK Pertiwi duwet. Sementara itu terdapat pula 4 (empat) instrumen atau teknik asesmen pada jenjang PAUD sebagai bagian utama dari konsep asesmen, yaitu : catatan anekdot, ceklis hasil karya, dan foto berseri.asesmen peserta didik pada mulai dari PAUD bisa melakukan berbagai cara, tidak seenaknya untuk menguasai tertentu.Kata kunci: Asesmen, Perkembangan, Anak Usia Dini